2007
DOI: 10.1007/s10750-006-0295-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the biota of Chany Lake along a salinity gradient

Abstract: Relationships among salinity and diversity, abundance, biomass of major biological components of Chany Lake (western Siberia, Russia) are examined across a salinity gradient. As salinity increased from 0.8 to 6.4 g l -1 , the species richness of aquatic vascular plants decreased from 16 to 2 species, of phytoplankton from 98 to 52 species, and of zooplankton from 61 to 16 species, but changes in species diversity of zoobenthos were negligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 12 publications
5
23
0
Order By: Relevance
“…The rest of sites did not show such clear habitat degradation; however, conductivity was high enough to reduce aquatic vegetation. These findings align with previous studies, which reported that most freshwater macrophyte species can be damaged by conductivities ranging from 1.5 to 3 mS cm -1 (Dunlop et al, 2005;Hart et al, 1991;James et al, 2003;Kipriyanova et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…The rest of sites did not show such clear habitat degradation; however, conductivity was high enough to reduce aquatic vegetation. These findings align with previous studies, which reported that most freshwater macrophyte species can be damaged by conductivities ranging from 1.5 to 3 mS cm -1 (Dunlop et al, 2005;Hart et al, 1991;James et al, 2003;Kipriyanova et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…In nature, increased salinity levels between 1 and 5 g dm − 3 cause a reduction in both species richness and abundance of zooplankton. Similar results were found by Kipriyanova et al (2007) who noticed a decrease in species richness of zooplankton from 61 to 16 species as salinity increased from 0.8 to 6.4 g dm − 3 . The hatching of resting eggs was inhibited at higher salinity levels between 16 and 32 g dm − 3 .…”
Section: Discussionsupporting
confidence: 89%
“…Such high salt concentrations can be toxic for water organisms (Cowgill and Milazzo 1990;Kipriyanova et al 2007). Most macroinvertebrates are able to live at salinity levels < 2 g dm − 3 , but for some macroinvertebrates, the salinity threshold is below 1 g dm − 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Since, throughout the study in Ojo de Agua Uriburu no predators were recorded and food availability (represented by phytoplankton chlorophyll-a) was always relatively high, the idea of a modulatory effect of salinity on the zooplankton community could be supported by the fact that richness was high while the lake remained in the mesosaline interval but declined once the lake surpassed the threshold of hypersalinity. Consequently, in the last two months of the sampling period, only the halotolerant B. poopoensis was found.This decrease in richness is consistent with that recorded in the Great Salt Lake (USA), where four species were recorded when salinity was close to 50 g L −1 but only one species was found when salinity was close to 250 g L −1 (Wurtsbaugh & Berry, 1990); and in the Siberian Lake Chany, where an increase in salinity from 0.8 g L −1 to 6.4 g L −1 caused a decrease in zooplankton richness from 61 to 16 species (Kipriyanova et al 2007). However, caution should be taken before reaching any conclusion, since the absence of significant statistical correlations among the studied environmental variables (water temperature and salinity), and the zooplankton parameters (density and biomass) is by no means a confirmation of a negative effect of increasing salinity on these biological parameters.…”
supporting
confidence: 89%